Electrical and optical characterization of p-type boron-doped 6H-SiC bulk crystals - Bickermann, Matthias; Weingärtner, Roland; Herro, Ziad Georges; Hofmann, Heinz-Dieter; Künecke, Ulrike; Wellmann, Peter; Winnacker, Albrecht (Materials Science Forum, 2003)
Electrical and optical characterization was performed to obtain information about the doping and compensation levels of samples cut from boron doped, physical vapor transport (PVT) grown 6H-SiC crystals. Values for N-A and N-D can be derived from analysis on temperature dependent Hall effect measurement data. The charge carrier concentration p at room temperature depends approximately linearly on N-A/N-D. The below band-gap absorption (BBGA) maximum at about 730 nm is correlated mainly to N-A, and, for constant N-A, is slightly anti-correlated to N-D. The same results can be obtained from an rootalpha vs. E plot extrapolated to alpha = 0 in the near band-gap region, as the broad absorption band induces a shift in the optically detected band-gap towards lower energies. Absorption measurements can give an estimation of N-A-N-D in boron doped SiC samples, and from wafers cut from the same crystal, the concentration of boron and compensating impurities can be evaluate
Keywords: Boron Doping; Hall-Effect; Homogeneous Incorporation; Optical Absorption; Optically Determined Band-Gap; p-Type SiC